A proteção multinível do direito à memória e à verdade: o caso das comissões subnacionais no Brasil - Coelho, Renata Santa Cruz (2016)
The intended dissertation is a critical reading of the effectiveness of the Transitional Justice, which cannot belittle the search for the right to memory and truth. Must be fought amnesia of companies that have gone through criminal state action, supporters of a political ideology. In addition, this fight is made exactly in exchange for truth from facts and the deconstruction of false versions of crimes committed by state agents. In this context, the effectiveness of the Transitional Justice shall, no doubt, by the action of truth commissions. However, these committees would be really an effective mechanism for the execution of a transitional justice? What are the practical effect of commissions? In the specific case, it would be possible to measure the effectiveness of the performance of commissions from the examination of processes and identification of the results? In other words, what were the benefits to society, with the establishment of truth commissions? In that, they effectively contribute to rescue the right to memory and truth and thus act in the transitional justice plan? Or was it only these representative committees of a formal institute to meet the formalities of the need for performance of the Brazilian State by virtue of his conviction by the Inter-American Court of Human Rights in the Araguaia case? This research work will seek to answer these questions, with a special focus on the role of sub-national committees. Investigates as well, as did the development, which is the composition, the methodology adopted for the examination of cases and, of course, the results obtained so far. Based on the examination of these data, we propose a reflection on the true role of truth commissions as a mechanism member of a Transitional justice system in search of their effectiveness.